Pengaruh Media Papan Huruf Terhadap Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun - Icam Sutisna; Sri Wahyuningsi Laiya; Magfira Pagatan (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The study formulation was to find out the use of Letter Board Media on Early Reading Ability for Children Aged 5-6 Years at TK Mekar Wangi Kindergarten in Botubarani Village, Kabila Bone District, Bone Bolango Regency, while the study objective seeks to determine the aforesaid formulation. This study employed a quantitative pre-experimental design (one-group pre-test-post-test design). The findings, with a sample of 15 children, indicated a significant difference in the average pre-test and post-test results. This can be seen in the pre-test data obtaining an average value of 24.13 and a standard deviation of 1.12. Meanwhile, the post-test data obtained an average value of 39.86 and a standard deviation of 3.62. The results show a significant influence before and after the treatment. Based on the output of the statistical test, it is known that the Tcount value is 16.2, and the Ttable value is 0.08. Therefore 16.2 > 0.088, thus, the hypothesis is accepted. Hence, the research hypothesis suggests that using letter board media influences the early reading ability of 5-6-year-old children at TK Mekar Wangi Kindergarten in Botubarani Village, Kabila Bone District, Bone Bolango Regency.